Community Participation in Village Development Planning: A Comparative Study In Bakambat And Cindai Alus Villages - Gina De Nisa (Journal of Transformative Governance and Social Justice, 2024)
Community participation is a crucial aspect of development planning. It allows the community to identify and address problems, ensuring that the resulting output aligns with the actual needs. This study aimed to examine the impact of community participation on development in two villages in Banjar Regency - Bakambat Village and Cindai Alus Village. The study involved 100 participants, with 50 from each village. A descriptive quantitative analysis method was employed, utilizing multiple linear regression methods. Data were collected through questionnaires and field observations, and processed using SPSS 25. The results revealed that the variables of Decision Making, Implementation, Benefits, and Evaluation did not significantly influence development in Bakambat Village. This suggests that other factors, such as human resources and economic factors, may play a more substantial role in development. In contrast, for Cindai Alus Village, while Decision-making, Implementation, and Evaluation did not significantly affect development, the Benefits variable did. This implies that the benefits received by the community can enhance community participation, thereby aiding in the improvement of development in Cindai Alus Village. In conclusion, while community participation is essential, its impact on development may vary depending on the context and other influencing factors. Therefore, a comprehensive understanding of these factors is necessary to effectively harness community participation for development.